Status and recent trends in coral reefs of the Philippines - Licuanan, Wilfredo Roehl Y. (Animo Repository, 2019)
Concern about the condition of Philippine coral reefs has prompted a recent reassessment of the status of the nation's reefs, the results of which are reported here. This paper presents the largest updated dataset on Philippine coral cover and generic diversity. The dataset was obtained from equally-sized sampling stations on fore-reef slopes of fringing reefs in six biogeographic regions using identical methods. A total of 206 stations were surveyed from 2014 to 2017, and another 101 stations were monitored from 2015 to 2018. The weighted average hard coral cover (HCC) was 22.8% (±1.2 SE) and coral generic diversity averaged 14.5 (±0.5 SE). Both were highest in the fully-formed reefs of the Sulu Sea biogeographic region and lowest in the eastern Philippines. Comparisons of findings with those of previous assessments show the continued decline in coral cover over a larger time scale, with the loss of about a third of the reef corals over the last decade. However, no consistent changes were evident in the 101 monitoring stations from 2015 to 2018 despite the global coral bleaching event. An expanded monitoring program, not just one-off assessments, is recommended to improve reef management in the Philippines. © 2019